Understanding sports coaching the pedagogical, social and cultural foundations of coaching practice - Cassidy, Tania 1964-; Jones, Robyn L.; Potrac, Paul 1974- (Routledge, Taylor & Francis Group, 2016)
Every successful sports coach knows that good teaching and social practices are just as important as expertise in sport skills and tactics. Now in a fully revised and updated third edition, Understanding Sports Coaching is still the only introduction to theory and practice in sports coaching to fully explore the social, cultural and pedagogical concepts underpinning good coaching practice. The book examines the complex interplay between coach, athlete, coaching programme and social context, and encourages coaches to develop an open and reflective approach to their own coaching practice. Understanding Sports Coaching also includes a full range of practical exercises and extended case studies designed to encourage coaches to reflect critically upon their own coaching strategies, their interpersonal skills and upon important issues in contemporary sports coaching. This is an essential textbook for any degree-level course in sports coaching, and for any professional coach looking to develop their coaching expertise.